Correction to: Waterlogging resistance and evaluation of physiological mechanism of three peach (Prunus persica) rootstocks. - Zhang, Binbin; Sun, Maoxiang; Liu, Wenxin; Lian, Min; Yang, Sankui; Peng, Futian; Xiao, Yuansong (Protoplasma, 2024)
This document is a correction notice for an article titled "Waterlogging resistance and evaluation of physiological mechanism of three peach (Prunus persica) rootstocks" published in the journal Protoplasma. The correction addresses the incorrect numbering of Figures 5, 6, and 7 in the published proof. The corrected figures depict the effects of waterlogging on cell death and ROS accumulation in the leaves of peach rootstocks and grafted seedlings. The original article has been corrected. The publisher, Springer Nature, remains neutral regarding jurisdictional claims and institutional affiliations.